Analisis Literasi Sains pada Buku Teks Pelajaran Kimia Kelas X Kurikulum Merdeka Belajar - Elim, Yohana; Salempa, Pince; Hasri, Hasri (Program Pasca Sarjana UNM, 2024)
This study is a qualitative descriptive study with the aim of knowing the scope of scientific literacy as knowledge, investigation of the nature of science, ways of thinking, and the interaction of Science Technology and society in chemistry textbook for year 10based on Merdeka Belajar Curriculum. The sample of this research is a science book of kurikulum merdeka which contains chemistry material from four different publishers. The scope of scientific literacy aspects of science as knowledge in chemistry textbooks foryear10 has a very high emergence of 63.35%. The scope of scientific literacy aspects of science as an investigation of the nature of Science in chemistry textbooks class X has the second highest occurrence of 27.57%.The scope of scientific literacy aspects of science as a way of thinking of chemistry textbooks for year 10 have the third largest occurrence of 6.37%. The scope of scientific literacy aspects of science as the interaction of Science Technology and society in chemistry textbooks for year 10 has the lowest occurrence of 2.71%.